Handwashing: a household social vaccine against COVID 19 and multiple communicable diseases - Parida, Swayam Pragyan; Bhatia, Vikas (International Journal of Research in Medical Sciences, 2020)
Handwashing is the most cost-effective measure for prevention of a wide spectrum of diseases from respiratory, intestinal, soil transmitted helminthiasis, health-care associated illness to infection with pandemic potential like SARS, MERS and COVID 19. Experts view that handwashing can be the greatest investment in the mankind as it reduces under nutrition, morbidity, mortality and paves way for growth, development, educational attainment of people and thereby achieving healthier communities. Though the evidence of handwashing on health is two centuries old but change in human behaviour seems critical in both developing and developed countries. Hand hygiene is rarely practiced during crucial moments and even rarely soap is used. Therefore emphasis should be given towards a societal shift in behaviour change among children, caretakers and people of all age groups. Every school, community and hospital should be provided with Safe water, Sanitation and adequate Hygiene (WASH) services. Hand hygiene to be given top priority in national health plans by which millions of unnecessary deaths and burden on health care system can be avoided. Nevertheless under the looming threat of the current COVID 19 pandemic, where the exact epidemiology is still evolving and a vaccine doesn’t seem feasible as an immediate measure to control the disease, handwashing should be considered as a ‘social vaccine’ for everyone at every household level.